2015
DOI: 10.1186/s12868-015-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

A 72-hour high fat diet increases transcript levels of the neuropeptide galanin in the dorsal hippocampus of the rat

Abstract: BackgroundRecent evidence identifies the hippocampus, a brain structure commonly associated with learning and memory, as key to the regulation of food intake and the development and consequences of obesity. Intake of a high fat diet (HFD) results in altered consumptive behavior, hippocampal damage, and cognitive deficits. While many studies report the effects of HFD after chronic consumption and in the instance of obesity, few examine the events that occur following acute HFD consumption. In this study, male r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
1
10
1
Order By: Relevance
“…The enhanced LTP and memory in the adult HFD-fed animals may be consistent with the recent findings that 3 days of HFD intake in adults resulted in increased hippocampal levels of galanin and brain-derived neurotrophic factor (BDNF) 38 , which are markers for neuroprotection and plasticity, respectively. Future studies should determine whether this up-regulation of galanin and BDNF in hippocampus could be the substrate that leads to enhancement of hippocampal plasticity and memory in adult animals following brief exposure to HFD.…”
Section: Discussionsupporting
confidence: 89%
“…The enhanced LTP and memory in the adult HFD-fed animals may be consistent with the recent findings that 3 days of HFD intake in adults resulted in increased hippocampal levels of galanin and brain-derived neurotrophic factor (BDNF) 38 , which are markers for neuroprotection and plasticity, respectively. Future studies should determine whether this up-regulation of galanin and BDNF in hippocampus could be the substrate that leads to enhancement of hippocampal plasticity and memory in adult animals following brief exposure to HFD.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, an important consideration in our model was the short-term restricted exposure and over-consumption of shortening in binge prone rats, which is a paradigm in which Bdnf pathway gene expression has not been widely studied and may explain the gene expression difference in our study. Consistent with this view, a study employing male rats fed 45% HFD for only 72 hours indicated a strong trend towards an increase in Bdnf mRNA expression in the dorsal hippocampus (p=0.059), despite no significant differences found in food intake, BW or body fat composition, as compared to the rats fed a control diet (10% fat by kcal) [77]. In another study, mice classified as diet induced obese (DIO) and diet induced resistant displayed differential expression of hippocampal Bdnf and TrkB genes when exposed to high fat, low fat or energy-restricted pair feeding diets [78].…”
Section: Discussionmentioning
confidence: 74%
“…It has been first described in 1999 [ 41 ] and since then shown in numerous studies that leptin is increased under the influence of HFD as compared to control diets in rats (e.g., [ 42 45 ]). It also has been shown in rats, using the same dietary regimen that HFD increases leptin levels [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown in rats, using the same dietary regimen that HFD increases leptin levels [ 12 ]. Leptin can even be increased in rats by HFD within 72 h independent of an increase in bodyweight [ 42 ]. Leptin has not been determined for the current analysis, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%